A novel method for manual weeding in row crops - SUNDARAM, PREM K; RAHMAN, A; SINGH, ANIL K; SARKAR, BIKAS (The Indian Journal of Agricultural Sciences, 2021)
For small and marginal farmers the affordable weeding option is either hand weeding or simple manual operated mechanical weeder in crop production for qualitative as well as quanlitative yield. Irrespective of weeding options the efficiency of weeding plays an importatnt role in overall performance of of the crop. This research paper presents a new prototype manual mechanical weeder designed and developed to take into account the anthropometric parameters of farm workers in Eastern region of India. Unlike other available manually operated mechanical weeders, this new weeder facilitates weeding in close proximity of plants and therefore improves overall wedding efficiency. The weeder was evaluated in maize crop and its weeding efficiency in maize crop was found to be 85% with operating field capacity 0.0120 ha/h. The design components of this weeder are simple and therefore can be manufactured locally at affordable and comparable with peers at cost of ₹1200-1400.